Notes on the uses of sport in Trump`s white nationalist assemblage - Kusz, Kyle W. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Using conjunctural analysis and informed by insights drawn from critical whiteness studies, sport studies, and masculinity studies, I offer some developing interpretations on two inter-related questions. First, how sport has been used to cultivate and popularize the proto-fascist white nationalist project(s) currently gripping the United States. And second, how sport facilitates the production and popularization of the unapologetic and omnipotent performance of white masculinity that seems central to the popular appeal of this contemporary American white nationalist assemblage.
Keywords: white nationalism; sport; masculinity; Trump, Donald John (prezydent Stanów Zjednoczonych; 1946- ); whiteness